Testosterone Suppression with Luteinizing Hormone‐Releasing Hormone (LHRH) Agonists in Patients Receiving Radiotherapy for Prostate Cancer. Issue 3 (7th February 2018) - Wilke, Derek; Patil, Nikhilesh; Hollenhorst, Helmut; Bowes, David; Rutledge, Robert; Ago, Casely
Abstract : Objectives: To characterize the probability of testosterone escape during a course of radiotherapy and androgen deprivation (ADT) in patients with prostate cancer, and examine predictors of testosterone escape, the prostate specific antigen (PSA) levels during testosterone escape, and the impact of testosterone escape on outcome. Patients and Methods: To participate in the database review, necessary data included: (i) type of luteinizing hormone‐releasing hormone agonist (LHRHa) administered, date of initiation, and date of cessation or duration of therapy, (ii) radiotherapy information (start date and dose) with at least 6 months of follow‐up after radiotherapy, (iii) radiotherapy to the prostate or prostate bed, and (iv) at least one serum testosterone and PSA measurement. Results: Five hundred sixty patients in the database were identified as being treated with radiotherapy and ADT. Three hundred seventy‐five patients had at least one measurement of testosterone and PSA, and the type of LHRHa used could be determined in 361 patients. Median follow‐up of patients still living was 4.7 years. The median number of testosterone measurements per patient was six. The incidence of testosterone escape per patient course of treatment was buserelin, 9.3%; goserelin, 10.5%; intramuscular leuprolide, 11.5%; leuprolide subcutaneous, 23.9%; and triptorelin, 6.7% (p = 0.02). There was no difference in either biochemical failure‐free survival or overall survival in patients stratified by testosterone escape. The modal PSA level during a testosterone escape was an undetectable PSA. Conclusions: An undetectable PSA does not rule out the presence of higher than desired levels of testosterone during ADT. In this cohort of patients, there appears to be no impact of testosterone escape on either biochemical relapse‐free survival or overall survival.